Internationalization of Moroccan SMEs. Literature review of different theoretical approaches and limits. - NEJJARI , Jihane; HASSINE , Mostafa (Revue Internationale des Sciences de Gestion, 2022)
Small and medium-sized enterprises are seen as an essential source of development and dynamism for all countries (Agndal, Chetty, 2007; Todd, Javalgi, 2007). Indeed, SMEs have gained the interest of researchers and can now be considered as a real object of study. Moreover, in recent years, Ribau, Moreira and Raposo highlighted the interest in the internationalization of small and medium-sized enterprises (SMEs) which is growing rapidly, mensionned in (child,2022), as their ability to do business globally has been perceived (HSBC, 2016). Internationalization has been characterized both as a cycle and to the extent that the exercises that companies embrace to go into international markets (Ribau et al., 2018). Welch and Luostarinen (1988) represent internationalization as "a more common way of expanding contribution to global tasks. As a cycle, it is not guaranteed that SME internationalization follows a fixed pattern of stages; on the contrary, various cases have been observed to present differentiated successions of opportunities (Jones, 1999). In this article, which focuses on the literature review of SME internationalization, we have proceeded by listing the different definitions of the concept of internationalization, and then we have listed the different approaches as well as their limitations.